THE INFLUENCE OF KNOWLEDGE SHARING AND WORK ETHIC ON INNOVATIVE WORK BEHAVIOR IS MEDIATED BY COLLABORATIVE CULTURE APPARATUS REGIONAL REVENUE AGENCY TOJO UNA-UNA REGENCY - Ilham; Idris; Adda, Harnida Wahyuni (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2025)
This study aims to determine and analyze the influence of Knowledge Sharing and Work Ethic on Collaborative Culture at the Regional Revenue Agency of Tojo Una-Una Regency; to determine and analyze the influence of Knowledge Sharing and Work Ethic on Innovative Work Behavior at the Regional Revenue Agency of Tojo Una-Una Regency; to determine and analyze the influence of Collaborative Culture on Innovative Work Behavior at the Regional Revenue Agency of Tojo Una-Una Regency; to determine and analyze the ability of Collaborative Culture in mediating the influence of Knowledge Sharing and Work Ethic on Innovative Work Behavior at the Regional Revenue Agency of Tojo Una-Una Regency. This study uses Structual Equation Modeling (SEM) analysis with SmartPLS version 4 software. The results of the study indicate that Knowledge Sharing and Work Ethic have a significant effect on Collaborative Culture at the Regional Revenue Agency of Tojo Una-Una Regency; Knowledge Sharing and Work Ethic have a significant effect on Innovative Work Behavior at the Regional Revenue Agency of Tojo Una-Una Regency; Collaborative Culture has a significant effect on Innovative Work Behavior at the Regional Revenue Agency of Tojo Una-Una Regency; Collaborative Culture can mediate the influence of Knowledge Sharing and Work Ethic on Innovative Work Behavior at the Regional Revenue Agency of Tojo Una-Una Regency.